2009
DOI: 10.1080/10903120802471956
|View full text |Cite
|
Sign up to set email alerts
|

Method of Cold Saline Storage for Prehospital Induced Hypothermia

Abstract: Prehospital refrigeration devices are needed for current and future IH protocols. Low-technology methods in the form of a cooler and ice packs can provide cold saline storage for longer than a full 24-hour shift in a room-temperature ambulance. In extremely hot conditions, 4 degrees C NSS can be maintained for nearly 11 hours using this method. This model exhibits an economical, easily deployable cold saline storage unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been shown that appropriate storage of coolant can be ensured by a conventional transportable cooler 11 12. Mader performed a pilot study, testing the temperature stability of 1000 ml NS bags isolated with a SIGG neoprene pouch (Neo+ group) or without one (Neo- group) 13.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that appropriate storage of coolant can be ensured by a conventional transportable cooler 11 12. Mader performed a pilot study, testing the temperature stability of 1000 ml NS bags isolated with a SIGG neoprene pouch (Neo+ group) or without one (Neo- group) 13.…”
Section: Discussionmentioning
confidence: 99%